Hepatic tuberculosis masquerading as cholangiocarcinoma: an unusual differential for a liver mass. Issue 8 (27th August 2020) - Maguire, Christopher; Sivabalan, Pirathaban; Jhamb, Shaurya; Palamuthusingam, Pranavan
Abstract: A 54-year-old woman presented with an incidentally identified asymptomatic liver lesion with imaging characteristics suspicious for malignancy. She underwent a left hemihepatectomy for presumed cholangiocarcinoma. Histopathology revealed granulomas with microbiological investigations later revealing a diagnosis of isolated hepatic tuberculosis. There were no pulmonary or other disease sites identified. The patient has been medically managed for primary hepatic tuberculosis and remains well postoperatively. This case identifies a rare differential for a liver mass that needs to be considered in the clinicians' workup.